Enhancing the shear strength of hybrid titanium-composite joints by out-of-plane protrusions - Wits, W.W.; Vos, C.J. de; Smit, M.J. de (SAMPE, 2025)
With the increasing usage of composite parts in aerospace, automotive and other sectors, there is a growing need for hybrid joining technologies. Innovation is desired in terms of joining methods to join metal and composite constituents. Traditional mechanical fastening methods, e.g. bolting and riveting, involve point contacts resulting in stress concentration, and labour and weight penalties. In this study, 3D-printed titanium is joined to unidirectional carbon fibre-reinforced thermoplastic composite. This type of joint is particularly challenging due to chemical incompatibility and mismatches of thermo-mechanical properties. The hybrid joint is constructed by hot press forming, as the heat and pressure control enable improved mechanical properties. Laser powder bed fusion is used to realize bespoke protrusions in the out-of-plane direction of the titanium faying surface that mechanically interlock with the composite material. Fabricated joints, with and without protrusions, are tensile tested in a single lap shear configuration. Results show that mechanical interlocking gives a 17x improvement compared to protrusion-free joints. The measured ultimate joint shear strength was on average 11.6 MPa. Moreover, this shear strength can be correlated to the feature size of the additively fabricated protrusions. Altogether, this gives valuable engineering insight for the design parameter optimisation of hybrid titanium-composite joints.